q-Double Cesaro Matrices and q-Statistical Convergence of Double Sequences - Çınar, Muhammed; Et, Mikail (Springer India, 2020)
In this study, we introduce and examine the concepts of q-double Cesaro matrices and q-statistical convergence and q-statistical limit point of double sequences. Also, we give some relations connected to these concepts.
ET, Mikail/0000-0001-8292-7819; Cinar, Muhammed/0000-0002-0958-0705
Keywords: q-Integers; Statistical convergence; Cesaro summability